Legal Protection For Cooperative Members in Standard Agreements On Digital Financial Services - Ni Luh Putu Sri Laksemi Dharmapadmi; Johannes Ibrahim Kosasih; I Made Arjaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to examine the Legal Protection for Cooperative Members in Standard Agreements on Digital Financial Services as well as the Legal Protection provided to Cooperative Members if there are problems with Digital Financial Services. The legal research method used by researchers is normative legal research. Normative legal research uses legal behavioral products, for example reviewing laws. The results of this research show that the legal protection provided to cooperative members regarding standard agreements is preventive legal protection, namely creating regulations in this case standard agreements and repressive legal protection aimed at resolving disputes arising from legal consequences. The legal remedies that can be taken are Litigation and Non-Litigation.